Secret wars : covert conflict in international politics - Carson, Austin (Princeton University Press, 2019)
Secret Wars is the first book to systematically analyze the ways powerful states covertly participate in foreign wars, showing a recurring pattern of such behavior stretching from World War I to U.S.-occupied Iraq. Investigating what governments keep secret during wars and why, Austin Carson argues that leaders maintain the secrecy of state involvement as a response to the persistent concern of limiting war. Keeping interventions “backstage” helps control escalation dynamics, insulating leaders from domestic pressures while communicating their interest in keeping a war contained.